ADMINISTRASI PENDIDIKAN DALAM MENGHADAPI KARAKTERISTIK DARI PARADIGMA PENDIDIKAN POLITIK - Nurharpani Nurharpani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: This study will explain the importance of the Political Education Administration Paradigm, which directs education to reflect on the dominant ideology towards socio-political transformation. Political education is education that seeks to create space to identify and analyze all the potential possessed by students freely and critically to realize the process of social transformation. The quality of education administration resulting from educational output is largely determined by the processes that occur in educational interactions. The whole process and method in education is based on the objectives to be achieved from the education. While the goals of education are determined based on the choice of paradigm that is used as the basis for education. From these assumptions, it can be seen how the paradigm in education is something that is fundamental and determines the results of education. Good and bad output from education is largely determined by the educational paradigm adopted.Keywords: Educational Administration, Characteristics, Paradigm, Political Education.